2013
DOI: 10.5120/12424-8973
|View full text |Cite
|
Sign up to set email alerts
|

Interference Simulation and Measurements for a Deployed 4G-WiMAX Network in an Urban Sub-Saharan African Environment

Abstract: WiMAX is a popular broadband solution with diverse applications. With several advantages such as low cost applications and last mile solution for broadband wireless access, WiMAX will no doubt help bridge the ever increasing digital divide in many SubSaharan African countries. Many countries Sub of the Sahara have recently started deploying WiMAX to offer subscribers affordable broadband internet service. Because of the peculiar conditions in Sub-Sahara Africa, critical design and optimization techniques will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
5
0
1
Order By: Relevance
“…There have been several attempts aimed at deploying 4G networks in Ghana. Earlier pilot deployment of LTE and WiMAX networks in Ghana suffered from high levels of cochannel and adjacent channel interference from co-located Third generation antenna systems [18]. This high level of interference led to low capacity networks with limited connectivity in earlier deployed networks.…”
Section: Networking Dimensioning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several attempts aimed at deploying 4G networks in Ghana. Earlier pilot deployment of LTE and WiMAX networks in Ghana suffered from high levels of cochannel and adjacent channel interference from co-located Third generation antenna systems [18]. This high level of interference led to low capacity networks with limited connectivity in earlier deployed networks.…”
Section: Networking Dimensioning Processmentioning
confidence: 99%
“…Where is the minimum sidelobe level value that is utilized to outline the search area for the effective SLL. The model in (18) will enable us determine the amount of added suppression required to reduce interference within the deployment area. The results of this solution will be used to determine appropriate sidelobe emission suppression factors during the deployment stage.…”
Section: B Antenna Beamwidth and Sidelobe Power Modellingmentioning
confidence: 99%
“…The SUI model estimates path loss using: for; The path loss exponent γ and standard deviation 's' are selected through statistical analysis. Log-normally distributed factor 's' denotes shadow fading due to environmental clutters on the transmission path having values within 8.2 dB -10.6 dB range [8]. The frequency correction factor and the correction factor for receiver antenna height for the models are:…”
Section: Stanford University Interim (Sui) Modelmentioning
confidence: 99%
“…The validity of the commonly used propagation models therefore becomes ineffective if they are applied on a terrain rather than the one originally used in deriving such models. Several studies conducted in Ghana and some tropical regions have revealed that a lot of the widely used path loss models have lower efficiency relative to the field measured values [2]. Hence, this makes it necessary to investigate most appropriate models that best fits the Ghanaian geographical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa penelitian berkaitan dengan interferensi radio frekuensi telah dilakukan, penelitian pertama membahas tentang total interferensi dalam jaringan dengan menggunakan simulasi monte carlo dengan hasil performa jaringan dievaluasi [4]. Penelitian kedua membahas tentang efek interferensi dan noise rise dari emisi spurious dampak dari performa coverage dan kapasitas sistem yang dikembang dengan hasil penggunaan strategi co-location channel spektrum bandwith antar operator [5].…”
unclassified